(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
In this article, Roman Ingarden’s concept of the strata of word sound in literary works is juxtaposed with the experiences of a scholarly editor. An attempt is made to reconsider this theory within the context of practical text preparation for publication, particularly in the modernisation of orthography and punctuation. The study also proposes extending the four strata of a literary work by incorporating an additional graphic stratum, which, in certain cases, directly correlates with the sonic dimension of poetic texts.